A REVIEW OF THE EXHAUST MUFFLERS USED IN AGRICULTURAL TRACTORS TO LOWER THE SOUND PRESSURE LEVEL - Kumar, Vijai; Bentham, John Robins; Kumar, Kshitij; Kumar, Kapil; Mohd. Murtaja; Singh, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In this review paper, different types of agriculture tractors exhaust muffler systems used to reduce the sound pressure level exhaust back pressure and effect of environmental conditions has been studied. The objective of the study waste decide the various parameters of exhaust muffler which reduces a large amount of sound pressure level with increase in exhaust back pressure and decrease in fuel consumption at different engine speeds. The results showed that combination type of exhaust muffler is more efficient than reactive and absorptive exhaust muffler. New designed exhaust muffler will be reducing sound pressure level tractor. Exhaust system is also preferable for new research work in agriculture tractor for better ergonomics and performance.